KEBIJAKAN UMUM IMPLEMENTASI MERDEKA BELAJAR - Tama Irhamsyah (Jurnal At-Tabayyun, 2023)
The implementation of the "Merdeka Belajar" (Freedom to Learn) policy is a crucial step in reshaping the education landscape in Indonesia. This policy aims to empower students to take charge of their own learning journey, fostering creativity, critical thinking, and a holistic development approach. This abstract provides an overview of the general policy framework, its objectives, and the anticipated impact on the education system. Key components include the decentralization of curriculum management, the integration of technology, and the promotion of lifelong learning. By examining the general principles and strategies of the "Merdeka Belajar" policy, this abstract contributes to a deeper understanding of the broader implications for education in Indonesia.